Comparison of high-dose and low-dose corticosteroid therapy for refractory Mycoplasma pneumoniae pneumonia in children. Issue 5 (May 2019) - ,; Miyajima, Yuji; Uno, Nozomi; Nagai, Noriko; Ando, Shotaro; Sudo, Yuji; Naruse, Kazuhisa; Takahashi, Yuma; Suzui, Ryosuke; Nagata, Yoshihiro; Kawabe, Takashi; Shibata, Motohiro; et al.
Abstract: Background: Mycoplasma pneumoniae pneumonia (MPP) is generally a self-limiting disease, but it may become refractory. It is thought that refractory MPP is linked to the excessive immunologic responses of the host. Consequently, the use of adjunctive systemic corticosteroids may have beneficial effects. In this study, we compared the effects of high- and low-dose corticosteroid therapy in a pediatric population with refractory MPP. Methods: We retrospectively collected data from 91 pediatric MPP patients treated with adjunctive systemic corticosteroids between April 2014 and October 2016. The patients were divided into the following two groups: high-dose corticosteroid group (2 mg/kg/day or more of prednisolone equivalents; n = 38) and low-dose corticosteroid group (<2 mg/kg/day; n = 53). Additionally, we compared the number of febrile days post-corticosteroid administration. We used 25 paired patients in a propensity score matching analysis to correct for confounding factors both by age and by days (from onset till corticosteroid therapy initiation). Results: We observed that in the high-dose corticosteroid group defervescence following corticosteroid therapy initiation was achieved significantly earlier and length of hospitalization was significantly shorter (0.8 ± 1.0 vs. 1.5 ± 1.4 days and 8.2 ± 2.4 vs. 10.7 ± 2.7 days, respectively). In the propensity score matching, we observed that significant differences in the length of fever following corticosteroid therapy initiation and hospitalization were still present. Further, neither of the groups developed corticosteroid-related adverse events. Conclusion: Our results suggest that patients with refractory MPP treated with high-dose corticosteroid could achieve defervescence earlier and have a shorter hospitalization.